Nosopsyllus (Nosopsyllus) spiniformis n. sp., a new ceratophyllid flea (Siphonaptera, Ceratophyllidae, Ceratophyllinae) from Türkiye - Keski̇n Adem (Zootaxa, 2024)
A new ceratophyllid flea species, Nosopsyllus (Nosopsyllus) spiniformis n. sp., is described and illustrated. Specimens were collected from Günther’s vole, Microtus guentheri (Danford & Alston), Schidlovsky’s vole, Microtus schidlovskii Argyropulo, in Adana province, and stone marten, Martes foina (Erxleben), in Tokat province. With the new species, the number of Nosopsyllus taxa known from Türkiye now tallies 11 (six species and five subspecies).